The Nature And Dimensions Of Human Personality In Islam - Moh. Toriqul Chaer; Sukatin Sukatin (Indonesia, 2022)
Talking about human beings means talking about the complexities within the human being. Alexis Carrel says that man is a mysterious creature because the degree of human separation from him is inversely proportional to his close attention to the world outside him. This opinion shows how difficult it is to understand human beings thoroughly. So that every time one finishes understanding from one aspect of human beings, then there is also another aspect. This article presents a discussion about human nature according to the text of the Quran, the dimension of Islamic personality. Gandhi states that Westerners have succeeded in achieving outstanding achievements for others (non-Western), but he thinks Western humans are incapable of reflecting on themselves, and this is enough to reveal the glaring failures of modern Western civilization.